Experimental, DFT Studies and Biological Evaluation of S‐methyl‐β‐N‐(3‐(2‐nitrophenyl)allylidene)dithiocarbazate. Issue 25 (4th July 2018) - Bhat, Rayees A.; Kumar, D.; Srivastava, Anurag; Mir, Bilal A.; Malla, Manzoor A.; Bhat, Muzzaffar A.; Mir, Muzzaffar A.
Abstract: S ‐Methyl‐ β‐N ‐(3‐(2‐nitrophenyl)allylidene)dithiocarbazate (HL), Schiff base of S‐ methyldithiocarbazate, was synthesized by 1:1 condensation between S‐ methyl dithiocarbazate and trans‐ o ‐Nitrocinnamaldehyde. It's in‐vitro cytotoxicity is assayed against two habitually infection causing bacteria strains including gram‐positive Staphylococcus aureus and gram‐negative Escherichia coli for antibacterial activity. The results showed appreciable biological activity and the activity increased with increase in concentration. This nitrogen‐sulfur based Schiff base (HL) was characterized by Mass, FT‐IR, 1 H‐NMR, 13 C‐NMR, Raman, and UV‐Vis spectroscopic techniques. Theoretical quantum chemical calculation has been performed using DFT in combination with B3LYP exchange correlation functional and 6‐311++ G (d, p) basis sets level. The computed parameters were: Chemical potential of compound ( μ ) −0.174 eV, HOMO‐LUMO energy gap −0.11093 eV, chemical hardness ( ɳ ) −0.055 eV, softness ( S ) 2.164 eV, ionization energy ( IE ) −0.23026 eV, electron affinity ( EA ) −0.11933 eV, the electronegativity ( EN ) 0.174 eV, dipole moment ( D ) 1.3383 Debye and relative stabilization energy −1536.982 eV . In the theoretical FT‐IR spectrum analysis 81 fundamental vibrational modes has be observed because of non‐linear structure of HL, with potential energy distribution percentage (PED%) by using VEDA‐4 (Vibrational energy distribution analysis) software. Theoretically calculated parameters like 1 H‐NMR, 13 C‐NMR, FT‐IR, UV‐VIS, Raman, electrostatic potential and HOMO‐LUMO energy gap were in conformity with experimental results. Abstract : Synthesized novel schiff base of dithiocarbazate namely S‐methyl‐β‐N‐(3‐(2‐nitrophenyl)allylidene)dithiocarbazate characterized by various spectroscopic techniques, which were compared with theoretical parameters performed by DFT (Gaussian 03), also found meticulous Zone of inhibition diameters against two commonly infecting bacterial strains.